2020
DOI: 10.4102/sajr.v24i1.1823
|View full text |Cite
|
Sign up to set email alerts
|

An audit of radiation doses received by paediatric patients undergoing computed tomography investigations at academic hospitals in South Africa

Abstract: Background: Diagnostic reference levels (DRLs) are a crucial element of auditing radiation doses in paediatric computed tomography (CT). Currently, there are no national paediatric CT DRLs in South Africa.Objectives: The aim of this article was to establish local paediatric DRLs for CT examinations at two academic hospitals and to compare paediatric CT radiation output levels with established DRLs in the developed and developing world.Method: Computed Tomography Dose Indexvolume (CTDIvol) and dose length produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…We compared our 75th percentile DRL values with local DRL values suggested by Van der Merwe et al as shown in Table 5 . 14 The CTDI vol values, except for 0–1 year and 1–5 year age groups, and DLP values for all age groups were higher than locally suggested DRLs, with the largest discrepancy observed in the 5–10 year and 10–15 year age groups. Thus the majority of patients in this audit were exposed to unnecessary high levels of ionising radiation, which could have long-term health implications.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…We compared our 75th percentile DRL values with local DRL values suggested by Van der Merwe et al as shown in Table 5 . 14 The CTDI vol values, except for 0–1 year and 1–5 year age groups, and DLP values for all age groups were higher than locally suggested DRLs, with the largest discrepancy observed in the 5–10 year and 10–15 year age groups. Thus the majority of patients in this audit were exposed to unnecessary high levels of ionising radiation, which could have long-term health implications.…”
Section: Discussionmentioning
confidence: 80%
“…Patients were divided into age groups (< 1 year, 1–5 years, 5–10 years and 10–15 years) and DRL values rounded to the nearest single digit for CTDI vol and nearest 5 for DLP, similar to Van der Merwe et al to compare the results with suggested local DRL values. 14 None of the patients in our study were aged 16 years, and thus this age group was not included in the age categories.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contrast agent used was Nucopark 320 mgL/mL, stored in a thermostatic box at 37°C. The volume CT dose index (CTDI vol ) and dose-length product (DLP) were recorded for all children, and the effective dose (ED) was calculated using the formula ED = DLP × k (k = 0.015) (5,6). Iodine intake was compared between the 2 groups as follows: For the control group, iodine intake (g) = contrast concentration (mgI/kg) × body weight (kg) × 2 mL/kg and, for the experimental group, iodine intake (g) = contrast concentration (mgI/kg) × body mass (kg) × 1.5 mL/kg.…”
Section: Equipment and Methodsmentioning
confidence: 99%